Urban amenities for creativity: An analysis of location drivers for photography studios in Nanjing, China. (April 2018) - He, Jinliao; Huang, Xianjin; Xi, Guangliang
Abstract: Urban amenities have been an increasing concern in recent scholarly discussion for their crucial role in promoting local economic development, especially for the rapid rise of the creative class. However, due to the Anglophone dominance in current discourse on this issue, the urban amenities for creativity in the particular context of China remain under-explored. This paper focuses on the location drivers for a specific sector of creative industries, photography studios, based at city level in Nanjing, China. It is suggested that urban amenities for creativity present great power to explain the spatial concentration of photography studios in the old downtown area of Nanjing. In general, photography entrepreneurship is closely associated with landscape amenities, leisure and networking amenities, and accessibility, whereas it is only slightly related to educational amenities. More specifically, the urban amenities for creativity for photography in Nanjing refer in particular to city gardens, cultural heritage, catering places, subway stations, locations which are relatively different from the attractions for creativity that are highlighted by the studies based in West. We therefore propose a contextualized and categorized approach for the urban policy of creative cities. Highlights: The question of "what are urban amenities for creativity" is raised by this paper The location drivers of photography studios in Nanjing is examined Photography entrepreneurship has a stronger spatial dependence on landscape amenities than on educational amenities A contextualized and categorized approach is required for urban policy of creative cities